2021
DOI: 10.3390/su13105757
|View full text |Cite
|
Sign up to set email alerts
|

Residential Location Choice in Istanbul, Tehran, and Cairo: The Importance of Commuting to Work

Abstract: The determinants of residential location choice have not been investigated in many developing countries. This paper examines this topic, including the influence of urban travels on house location decision-making in the Middle East and North Africa (MENA). Based on 8284 face-to-face interviews in Istanbul, Tehran, and Cairo, the dummy variable of residential location choice, including two categories of mobility reasons and other factors, was modeled by binary probit regression modeling. By means of receiver-ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Another reflection concerns the methodology followed in the MENA and SA regions' transportation research; it tends to be more descriptive and limited conclusions are found based on empirical modeling results apart from a few exceptions (Soltanzadeh and Masoumi, 2014;Etminani-Ghasrodashti and Ardeshiri, 2016;Soltani and Shams, 2017;Etminani-Ghasrodashti and Hamidi, 2019;Masoumi, 2020Masoumi, , 2021Masoumi, , 2022Mehriar et al, 2020;Javid et al, 2021;Masoumi et al, 2021). The spatial data availability and analysis remains a challenge for most of the cities in the MENA and SA regions basically due to non-availability of updated information in a single repository and also hesitancy to share the information by the governing authorities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reflection concerns the methodology followed in the MENA and SA regions' transportation research; it tends to be more descriptive and limited conclusions are found based on empirical modeling results apart from a few exceptions (Soltanzadeh and Masoumi, 2014;Etminani-Ghasrodashti and Ardeshiri, 2016;Soltani and Shams, 2017;Etminani-Ghasrodashti and Hamidi, 2019;Masoumi, 2020Masoumi, , 2021Masoumi, , 2022Mehriar et al, 2020;Javid et al, 2021;Masoumi et al, 2021). The spatial data availability and analysis remains a challenge for most of the cities in the MENA and SA regions basically due to non-availability of updated information in a single repository and also hesitancy to share the information by the governing authorities.…”
Section: Methodsmentioning
confidence: 99%
“…Among MENA cities, a couple of major empirical studies were completed recently for Tehran and Cairo (Mehriar et al, 2020;Masoumi, 2021Masoumi, , 2022. Etminani-Ghasrodashti and Hamidi (2019) found in Tehran that individuals who prefer driving and semipublic transit also have a higher number of Snapp trips than other demographics.…”
Section: Traditional Public Transport and Emerging Shared Mobility Modesmentioning
confidence: 99%
“…Masoumi (2019) observed that residential location choices play a vital role in mode choice selection in Tehran, Istanbul, and Cairo [26]. In one of his recent studies for the same case study areas, Masoumi (2021) identified neighborhood characteristics, accessibility, commuting distance, public transit trips, and individual characteristics such as age and driving license that affect the residential location choice [27]. Masoumi (2013) also found a significant role of socioeconomics in determining the residential location choices in Tehran, Iran [28].…”
Section: Correlates Of Residential Location Choicesmentioning
confidence: 99%
“…The choice of a location is the outcome of the household's preferences and what is offered in the housing market. These preferences come from the culture and lifestyle, which vary based on geographical context (Masoumi, 2021). Moreover, the local housing market of a particular urban area also varies in terms of neighborhood characteristics, and the supply depends on the local housing interventions by public institutions based on the housing market situation.…”
Section: Introductionmentioning
confidence: 99%